Clean and Healthy Living Behavior (PHBS) Among Marginal Children In Jakarta - Ulfa Diya Atiqa (Hayyan Journal, 2024)
Clean and healthy living behavior is an action to maintain personal hygiene, well-being, physical and psychological to improve health. Marginal children are identified as a community that receives less attention regarding healthy living behavior, especially personal hygiene. This disrupts their daily lives, especially the need for personal hygiene. This study aims to determine the behavior of knowledge about personal hygiene, body image, social support, and the availability of facilities at home. This study uses a qualitative approach. Determination of informants using purposive sampling techniques. Data collection through in-depth interviews using interview guides. The survey results show that there are some marginal children who already know about it but have not fully understood it. The body image of marginal children that they believe in the clothes they wear every day, want to look attractive. The emotional role of parents towards marginal children who support children to always maintain personal hygiene. In addition, supporting facilities in the implementation of good personal hygiene are still not available in children's houses.